2018
DOI: 10.1016/j.rgmx.2017.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Aplicación de la endoscopia sistemática alfanumérica codificada más cromoendoscopia para la detección de lesiones precancerosas gástricas y cáncer gástrico temprano en sujetos con riesgo promedio de cáncer gástrico

Abstract: Both techniques were effective, but systematic alphanumeric-coded endoscopy significantly reduced the false positive rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Indigo carmine can be applied directly to the mucosa. Another important type of endoscopy that is constantly developing is highresolution imaging -magnifying endocscopy [10]. One study, however, has shown that second-generation narrow band imaging (2G-NBI) did not increase the early gastric cancer detection rate over conventional endocsopy.…”
Section: Types Of Screening Methodsmentioning
confidence: 99%
“…Indigo carmine can be applied directly to the mucosa. Another important type of endoscopy that is constantly developing is highresolution imaging -magnifying endocscopy [10]. One study, however, has shown that second-generation narrow band imaging (2G-NBI) did not increase the early gastric cancer detection rate over conventional endocsopy.…”
Section: Types Of Screening Methodsmentioning
confidence: 99%